battery
Patent Information
- Application Number
- CN202610968661.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-13
AI Technical Summary
然而,该材料在实际应用中面临一个关键瓶颈:在反复充放电过程中,其体积膨胀率高达300%
(1) 本发明通过在正极活性层表面围绕正极极耳槽设置第一表涂层,缓解热量传递和扩散,将正极活性层和电解液隔离,减少电解液副反应及副反应产物对正极稳定性的影响,提升电池的热箱安全性能;同时,在正极活性层中引入高离子电导率的固态电解质材料,缓解表涂层的设置对正极片动力学性能产生的影响;
Smart Images

Figure CN122907705A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and more specifically to a battery. Background Technology
[0002] As lithium-ion batteries continue to evolve towards higher capacity and energy density, silicon-carbon anode materials have attracted much attention due to their ultra-high theoretical specific capacity. However, this material faces a key bottleneck in practical applications: its volume expansion rate reaches as high as 300% during repeated charge-discharge cycles. This drastic volume change not only easily leads to repeated rupture and reconstruction of the solid electrolyte interphase (SEI) film on the anode surface, but may also induce lithium plating side reactions, thereby posing a serious threat to the thermal stability of the battery. Therefore, how to effectively improve its safety in hot-box testing while ensuring the basic electrochemical performance of the battery has become a key problem that urgently needs to be solved to promote the industrial application of silicon-carbon anode materials. Summary of the Invention
[0003] The purpose of this invention is to provide a battery that significantly improves the pass rate in hot box testing and optimizes the thermal safety performance of silicon-carbon anode system batteries without affecting kinetic performance.
[0004] Silicon-carbon anodes significantly improve battery capacity and energy density. However, silicon-carbon materials undergo dramatic volume expansion during battery cycling. Internal expansion stress causes the SEI film at the anode to continuously rupture and regenerate, exacerbating electrolyte side reactions. This further intensifies internal heat and gas generation, and slows heat dissipation. The migration of byproducts from these side reactions to the cathode exacerbates the degradation of the cathode's structural stability. During hot-box testing, external heat is transferred from the tabs to the battery interior. This causes thermal contraction of the separator at high temperatures, increasing the risk of thermal runaway. Furthermore, it reduces the stability of the cathode active material. At high temperatures, significant heat accumulates at the tab location, increasing the risk of decomposition and recombination of the surface of the cathode active layer and the solid electrolyte membrane. This intensifies side reactions between the cathode material and the electrolyte in this region, leading to increased heat generation and more byproducts (such as HF). These byproducts accelerate the structural degradation and oxygen release of the cathode active material, further exacerbating gas and heat generation, leading to a further increase in the battery's internal temperature. All of these factors significantly increase the risk of battery thermal runaway. In related technologies, a surface coating is applied to the surface of the positive electrode to effectively reduce heat transfer through the positive electrode surface at high temperatures and isolate the electrolyte from direct contact with the positive electrode active material, thereby improving the thermal stability of the battery at high temperatures. However, good thermal stability also requires the surface coating to have sufficient thickness, which leads to an increase in the proportion of non-active materials in the battery, which is not conducive to improving the energy density of the battery. At the same time, it also increases the transport resistance of lithium ions in the surface coating, resulting in insufficient lithium ion solid-phase diffusion capacity in the area where the surface coating is applied, affecting the dynamics of the positive electrode, causing an imbalance between the supply and demand of lithium ions between the positive and negative electrodes, and increasing the risk of lithium deposition on the negative electrode side.
[0005] Through extensive experimental research, the inventors of this invention discovered that during hot box testing, the ambient temperature in the hot box is transferred to the battery interior through the tabs. That is, external heat accumulates at the tabs and then spreads along the surrounding area. The internal heat of the battery needs to be dissipated to the environment through its surface in a timely manner to prevent excessive temperature increases. However, the tab surface is generally covered by multiple layers of adhesive paper and separators, and the materials have poor thermal conductivity in the vertical direction, making it difficult for heat to be quickly transferred to the battery surface. Therefore, heat accumulates significantly at and around the tabs and is difficult to dissipate. The separator corresponding to this area is also more prone to heat loss at high temperatures. High temperatures, especially at the positive electrode tab, significantly impact the stability of the positive electrode active material. This is because high temperatures cause the solid electrolyte membrane on the positive electrode active layer near the tab to decompose, increasing side reactions between the positive electrode active material and the electrolyte in this area. Simultaneously, high temperatures make the positive electrode active material more prone to structural degradation, releasing oxygen and exacerbating the heat increase at the tab, creating a vicious cycle that further deteriorates the battery's thermal safety. Furthermore, during thermal testing and high-temperature cycling, the increased ambient temperature accelerates the oxidative decomposition of the electrolyte, leading to accelerated decomposition and consumption of the electrolyte near the tab, thus reducing the battery's electrical performance. Therefore, by specifically applying the first surface coating to the area adjacent to the positive electrode tab groove, optimization can be achieved for areas with high heat accumulation in the positive electrode sheet. This reduces membrane shrinkage and side reactions in the high-temperature positive electrode tab and its vicinity. The first surface coating covers the local surface of the positive electrode active layer, isolating the positive electrode active layer and the electrolyte, inhibiting direct contact between the positive electrode active layer and the electrolyte, reducing electrolyte side reactions, alleviating gas and heat generation, and fundamentally mitigating the heat increase at the tab location. When the battery is in a high-temperature environment, the separator corresponding to the tab location is prone to thermal shrinkage. The first surface coating can partially act as a separator, separating the positive and negative electrodes and preventing direct contact between them when the separator undergoes thermal shrinkage, thus improving battery safety. While a suitable surface coating thickness h1 can improve the battery's thermal stability, when the surface coating thickness h1 increases to a certain extent, it leads to a decrease in the lithium-ion transport rate at the positive electrode, which is detrimental to the improvement of battery kinetics. This problem can be effectively improved by introducing a solid electrolyte into the positive electrode active layer. This is because solid electrolytes typically have high ionic conductivity. When mixed into the positive electrode active layer, they can fill the gaps between the positive electrode active material particles, providing a pathway for lithium ion transport between particles. Lithium ion transport can be optimized by adjusting the average particle size R1 of the solid electrolyte material. When R1 is at a low level, the kinetic performance of the positive electrode can be further improved by shortening the transport path of lithium ions in the solid electrolyte.
[0006] During their research, the inventors of this invention discovered that the introduction of solid-state electrolytes improves the kinetic performance of the positive electrode, increasing its reactivity. However, small-particle-size solid-state electrolytes have a higher specific surface area, increasing the effective contact area with the electrolyte, catalyzing electrolyte decomposition, and increasing battery gas and heat generation. Simultaneously, this leads to a decrease in the structural stability of the positive electrode active material. This is because the increased specific surface area of small-particle-size solid-state electrolytes results in more alkaline sites or an increased risk of phosphate exposure. These alkaline sites can catalyze the removal of oxygen from the surface of the positive electrode material (e.g., lithium cobalt oxide, nickel-cobalt-aluminum ternary materials, nickel-cobalt-manganese ternary materials), promoting oxygen release. The dissolved phosphate reacts with the positive electrode transition metals (e.g., Ni, Co, Mn), disrupting the structural stability of the positive electrode and causing instability in the positive electrode active material. This release of oxygen, along with the violent reaction of the released active oxygen with the electrolyte, exacerbates the side reactions between the positive electrode active material and the electrolyte, accelerating thermal runaway. Conversely, while increasing the thickness of the coating layer can improve the battery's thermal safety performance, it degrades the kinetic performance of the positive electrode. Therefore, independently adjusting the average particle size R1 of the solid electrolyte or the thickness h1 of the coating layer cannot simultaneously improve kinetic performance and increase the pass rate of the hot box test. Only by adjusting R1 and h1 at the same time can the improvement of the hot box safety performance by the coating layer and the optimization of the cathode kinetic performance by the solid electrolyte work synergistically to maximize the effect.
[0007] Based on this, the present invention proposes the following technical solution: This invention provides a battery comprising an electrode assembly wound with a positive electrode, a separator, and a negative electrode. The positive electrode includes a positive current collector and positive active layers located on both sides of the positive current collector. The negative electrode includes a negative current collector and negative active layers located on both sides of the negative current collector. The positive active layer includes a solid electrolyte material with a median particle size Dv50 of R1, where R1 is 0.1 μm to 5 μm. The negative active layer includes a negative active material, which is packaged... The cathode material includes silicon-carbon material; the cathode includes a first surface and a second surface disposed opposite to each other along the thickness direction, the first surface being provided with a cathode tab groove exposing the cathode current collector; the cathode also includes a first surface coating, which is located on the side of the cathode active layer away from the cathode current collector along the thickness direction of the cathode, and the first surface coating includes a first portion disposed around the cathode tab groove; the thickness of the first surface coating is h1, and h1 and R1 satisfy: 0.15≤h1 / R1≤60.
[0008] By employing the above technical solution, the present invention has at least the following advantages compared with the prior art: (1) The present invention provides a first surface coating around the positive electrode tab groove on the surface of the positive electrode active layer to alleviate heat transfer and diffusion, isolate the positive electrode active layer and electrolyte, reduce the impact of electrolyte side reactions and side reaction products on the stability of the positive electrode, and improve the thermal safety performance of the battery; at the same time, a solid electrolyte material with high ionic conductivity is introduced into the positive electrode active layer to alleviate the impact of the surface coating on the dynamic performance of the positive electrode sheet; (2) This invention optimizes ion transport and improves the dynamics of the positive electrode by adjusting the specific relationship between the average particle size of the solid electrolyte and the thickness of the coating, while also taking into account the safety performance of the hot box. (3) The battery of the present invention combines thermal box safety performance and good dynamic performance.
[0009] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. Attached Figure Description
[0010] Figure 1 The diagram shown is a schematic diagram of the positive electrode sheet along the thickness direction in one embodiment of the present invention.
[0011] Figure 2 The figure shown is a planar schematic diagram of the positive electrode sheet in one embodiment of the present invention.
[0012] Reference numerals: 101, first surface; 102, second surface; 11, positive current collector; 12, positive active layer; 13, first surface coating; 131, first part; 132, second part; 14, second surface coating; 141, third part; 142, fourth part; 151, positive electrode tab groove; 152, first groove; 16, positive electrode tab. Detailed Implementation
[0013] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.
[0014] The present invention provides a battery comprising an electrode assembly formed by winding a positive electrode, a separator, and a negative electrode, wherein the positive electrode includes a positive current collector and a positive active layer located on both sides of the positive current collector, and the negative electrode includes a negative current collector and a negative active layer located on both sides of the negative current collector.
[0015] In this invention, the positive electrode active layer comprises a solid electrolyte material, wherein the median particle size Dv50 of the solid electrolyte material is R1, and R1 is 0.1μm to 5μm, for example, 0.1μm, 0.2μm, 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm or 5μm.
[0016] In one embodiment, R1 is 0.5 μm to 3 μm.
[0017] In this invention, the negative electrode active layer includes a negative electrode active material, which includes a silicon-carbon material.
[0018] In this invention, the positive electrode sheet includes a first surface and a second surface disposed opposite to each other along the thickness direction, and the first surface is provided with a positive electrode tab groove that exposes the positive electrode current collector.
[0019] In this invention, the positive electrode sheet further includes a first surface coating layer. Along the thickness direction of the positive electrode sheet, the first surface coating layer is located on the side of the positive electrode active layer away from the positive electrode current collector. The first surface coating layer includes a first portion disposed around the positive electrode tab groove.
[0020] It is understood that the first portion of the first surface coating is located on at least a portion of the second surface, wherein "at least a portion" can be understood as the percentage of the orthographic projection area of the first portion of the first surface coating on the first surface being greater than 0%, less than 100%, or equal to 100%.
[0021] In this invention, the positive electrode sheet includes a positive electrode tab located within the positive electrode tab groove.
[0022] In this invention, along the length direction of the positive electrode sheet, the positive electrode tab groove has a first side and a second side arranged opposite to each other; along the width direction of the positive electrode sheet, the positive electrode tab groove has a third side and a fourth side arranged opposite to each other; the positive electrode sheet has an upper end face close to the extension direction of the positive electrode tab and a lower end face away from the extension direction of the positive electrode tab; the third side is close to the upper end face, and the fourth side is close to the lower end face; the first part of the first surface coating is arranged around the positive electrode tab groove, which can be understood as the first part being adjacent to the first side, the second side and the fourth side.
[0023] In this invention, the thickness of the first surface coating is h1, and h1 and R1 satisfy: 0.15≤h1 / R1≤60, for example, 0.15, 0.2, 0.3, 0.5, 1, 1.5, 2, 3, 4, 6, 8, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55 or 60.
[0024] In one embodiment, h1 and R1 satisfy: 1≤h1 / R1≤6.5.
[0025] Introducing a solid electrolyte into the positive electrode active layer can improve the overall kinetic performance of the positive electrode by utilizing its high ionic conductivity, while reducing the impact of the coating layer's placement and thickness on lithium-ion transport. Adjusting R1 within the range of 0.1 μm to 5 μm ensures that the solid electrolyte particles are uniformly dispersed in the positive electrode active layer, avoiding unevenness and increased interfacial impedance caused by large particles (e.g., R1 > 5 μm), or agglomeration of small particles (e.g., R1 < 0.1 μm) that hinders ion conduction, both of which are detrimental to improving battery rate performance.
[0026] By setting the first part of the first coating around the positive electrode tab groove and introducing a solid electrolyte with high ionic conductivity into the positive electrode active layer, the effect of heat accumulation at the tab position on battery performance can be improved in the area with the greatest heat impact. It can also protect the positive electrode active material located in the area near the positive electrode tab groove from the side reactions and by-products of the electrolyte, ensuring that the battery heat box throughput is improved while also having good rate performance. Adjusting h1 and R1 within appropriate ranges can further optimize the stability and kinetic performance of the positive electrode. When h1 / R1 is too small (e.g., <0.15), h1 is too small compared to R1, which may cause solid electrolyte particles to protrude from the surface of the first surface coating. This reduces the surface smoothness and continuity of the first surface coating, leading to an increase in the interfacial resistance between the first surface coating and the positive electrode active layer. Simultaneously, it reduces the bonding tightness between the positive electrode active layer and the first surface coating, preventing the first surface coating from reducing side reactions between the positive electrode active layer and the electrolyte in areas with high local temperatures on the electrode. This is detrimental to further improving the battery's thermal conductivity and high-temperature cycling stability. Excessively large solid electrolyte particles have a small specific surface area and cannot effectively fill the spaces between the positive electrode active material particles. In the gap, the contact area with the positive electrode active material is small, and the improvement in lithium-ion transport efficiency between particles is not significant, which is not conducive to further improvement of positive electrode kinetics and thermal pack throughput. When h1 / R1 is too large (e.g., >60), h1 is too large compared to R1, the first surface coating is too thick, and the transport distance of lithium ions in the first surface coating is too large. Even if a solid electrolyte is introduced into the positive electrode active layer, it cannot take advantage of its high ionic conductivity, and the improvement on positive electrode kinetics is limited, which is not conducive to improving the rate performance of the battery. In addition, when R1 is small, although it can improve the lithium-ion transport rate, its specific surface area is large and the alkaline sites increase, which will further reduce the structural stability of the positive electrode active material, thus not conducive to further improving the thermal pack throughput and high-temperature cycle stability of the battery.
[0027] In this invention, h1 is 0.5μm to 12μm, for example, 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 8μm, 10μm or 12μm.
[0028] In one embodiment, h1 is 1 μm to 8 μm.
[0029] In this invention, the second surface of the positive electrode sheet is provided with a first groove, and the first groove and the positive electrode tab groove are disposed opposite to each other along the thickness direction of the positive electrode sheet; the first surface coating also includes a second part disposed around the first groove.
[0030] In this invention, along the length direction of the positive electrode sheet, the first groove has a fifth side and a sixth side disposed opposite to each other; along the width direction of the positive electrode sheet, the first groove has a seventh side and an eighth side disposed opposite to each other; the positive electrode sheet has an upper end face close to the extension direction of the positive electrode tab and a lower end face away from the extension direction of the tab; the seventh side is close to the upper end face and the eighth side is close to the lower end face; the second part of the first surface coating is disposed around the first groove, which can be understood as the second part being disposed adjacent to the fifth side, the sixth side and the eighth side.
[0031] It is understood that the second portion of the first surface coating is located on at least a portion of the second surface, wherein "at least a portion" can be understood as the percentage of the projected area of the second portion of the first surface coating on the second surface being greater than 0%, less than 100%, or equal to 100%.
[0032] In this invention, along the length direction of the positive electrode sheet, the ratio of the width of the positive electrode tab groove to the width of the first portion is 0.05 to 0.5, for example, 0.05, 0.06, 0.08, 0.1, 0.15, 0.2, 0.25, 0.3, 0.4 or 0.5.
[0033] In this invention, along the length direction of the positive electrode sheet, the ratio of the width of the second groove to the width of the second portion is 0.05 to 0.5, for example, 0.05, 0.06, 0.08, 0.1, 0.15, 0.2, 0.25, 0.3, 0.4 or 0.5.
[0034] In this invention, h1 can be determined by conventional testing methods in the art, such as by scanning electron microscopy (SEM), specifically as follows: discharge the battery to 0% SOC, disassemble and remove the positive electrode sheet, soak it in dimethyl carbonate (DMC) solvent for 12 hours, then rinse it with DMC solvent to remove the lithium salt attached to the positive electrode sheet, dry it, take the positive electrode sheet with the positive electrode tab groove, polish its cross-section with an argon ion polisher, image the obtained cross-section in the scanning electron microscope (SEM), locate the first surface coating and randomly select at least 10 different points, and then use image analysis software (such as Image J) to determine the thickness of the first surface coating, and take the average value as h1.
[0035] In this invention, R1 can be determined using conventional testing methods in the art, such as SEM equipment, specifically as follows: The battery is discharged to 0% SOC, the positive electrode is disassembled and removed, soaked in dimethyl carbonate (DMC) solvent for 12 hours, then rinsed with DMC solvent to remove lithium salts adhering to the positive electrode. After drying, the positive electrode is cut using an argon ion mill, and the cross-section of the positive electrode is observed using SEM. The obtained cross-section is magnified to a certain factor (e.g., 5000x), and the maximum diameter of at least 30 solid electrolyte particles is determined using image analysis software (such as ImageJ). The average value is taken as R1. If the number of solid electrolyte particles is less than 30 at 5K magnification, the cross-section of the positive electrode is moved until the maximum diameter of 30 solid electrolyte particles can be measured.
[0036] In this invention, the width of the positive electrode tab groove and the width of the first part can be determined by conventional testing methods in the art. For example, the battery is discharged to 0% SOC, the positive electrode sheet is disassembled and taken out, soaked in dimethyl carbonate (DMC) solvent for 12 hours, and then rinsed with DMC solvent to remove the lithium salt attached to the positive electrode sheet. After drying, the positive electrode sheet with the positive electrode tab groove is taken, the width of the positive electrode tab groove is measured with a ruler, and the width of the first part is measured with a 3D microscope.
[0037] In this invention, the negative electrode sheet includes a third surface and a fourth surface disposed opposite to each other along the thickness direction, wherein the third surface is provided with a negative electrode tab groove that exposes the negative electrode current collector, and the negative electrode sheet also includes a negative electrode tab located in the negative electrode tab groove.
[0038] In this invention, the positive electrode sheet further includes a second surface coating layer located on the surface of the positive electrode active layer away from the positive electrode current collector. The second surface coating layer includes a third portion. Along the thickness direction of the battery, the third portion and the negative electrode tab groove are disposed opposite each other. Along the thickness direction of the negative electrode sheet, the orthographic projection of the third portion and the negative electrode tab groove on the surface of the positive electrode sheet at least partially overlaps. "At least partially overlaps" means that the overlap rate between the orthographic projection of the third portion of the second surface coating layer and the negative electrode tab groove on the surface of the positive electrode sheet is greater than 0%, and can be less than 100% or equal to 100%. Preferably, the orthographic projection of the third portion covers the orthographic projection of the negative electrode tab groove on the surface of the positive electrode sheet.
[0039] In some embodiments, the fourth surface of the negative electrode sheet is further provided with a second groove. Along the thickness direction of the negative electrode sheet, the second groove and the negative electrode tab groove are disposed opposite to each other. The second surface coating also includes a fourth portion. Along the thickness direction of the battery, the fourth portion and the second groove are disposed opposite to each other, and the orthographic projections of the fourth portion and the second groove on the surface of the positive electrode sheet at least partially overlap. Here, "at least partially overlap" means that the overlap rate of the orthographic projections of the fourth portion and the second groove on the surface of the positive electrode sheet is greater than 0%, and can be less than 100% or equal to 100%. Preferably, the orthographic projection of the fourth portion covers the orthographic projection of the second groove on the surface of the positive electrode sheet.
[0040] It is understood that the third portion and the negative electrode tab groove are disposed opposite to each other on both sides of the diaphragm along the thickness direction of the diaphragm. The third portion and the second groove are disposed opposite to each other on both sides of the diaphragm along the thickness direction of the diaphragm.
[0041] like Figure 1 The diagram shown is a schematic representation of the positive electrode sheet along its thickness in one embodiment of the present invention; as shown... Figure 2 The figure shown is a planar schematic diagram of the positive electrode sheet in one embodiment of the present invention.
[0042] Silicon-carbon anodes are highly effective in improving battery capacity and energy density. However, silicon-carbon materials undergo dramatic volume expansion during battery cycling. The internal expansion stress causes the SEI film at the anode to continuously rupture and regenerate. This process not only leads to the continuous generation of fresh interfaces, exacerbating side reactions between the electrolyte and silicon-carbon materials, but also causes the SEI film thickness to increase and form a high-resistance interface. This increases the resistance to lithium ion transport in the SEI film, preventing lithium ions from successfully intercalating into the silicon-carbon material. Consequently, the deposition of lithium ions on the anode surface is uneven and prone to inducing lithium plating. At the same time, the dramatic volume expansion may also damage the structure of the silicon-carbon material, causing the conductive network in the anode sheet to break. This hinders the intercalation of lithium ions into the silicon-carbon material, and some lithium ions precipitate on the anode surface, resulting in lithium plating. When lithium plating occurs on the negative electrode surface, the battery's internal resistance increases. During charging and discharging, the battery's heat generation rises sharply. The increased ambient temperature, in turn, accelerates the electrolyte's side reactions. The generated heat is transferred from the tabs to the battery's interior, further intensifying internal heat and gas generation. Slow heat dissipation leads to thermal shrinkage of the separator at high temperatures, increasing the risk of thermal runaway. Furthermore, it reduces the stability of the positive electrode active material. This is because at high temperatures, heat accumulates significantly at the positive electrode tab, increasing the risk of decomposition and recombination of the positive electrode active layer surface and the solid electrolyte membrane at this location. This intensifies the side reactions between the positive electrode material and the electrolyte in this region, increasing heat generation and the production of side reaction products (such as HF). These products accelerate the structural degradation and oxygen release of the positive electrode active material, further exacerbating gas and heat generation, leading to a further increase in the battery's internal temperature. All of these factors significantly increase the risk of battery thermal runaway. The area where the negative electrode tab is located is also a relatively concentrated area of heat. The separator, which is positioned opposite the negative electrode tab groove, is prone to thermal shrinkage during hot box testing or when the battery temperature rises. This can lead to a decrease in the battery's hot box safety performance and make it prone to thermal runaway during battery cycling. Even if the degree of separator shrinkage does not cause a short circuit between the positive and negative electrodes, the separator will still have its pore structure destroyed due to shrinkage, and the lithium-ion transport channels will be blocked, further aggravating lithium plating in the area where the negative electrode tab is located.
[0043] Furthermore, a second surface coating is applied to the surface of the positive electrode active layer. On one hand, this coating can isolate the positive electrode active layer and the electrolyte in the area opposite to the negative electrode tab groove (or the second groove), reducing the decrease in the stability of the positive electrode active material structure on the opposite side of the negative electrode tab due to excessive heat accumulation at the negative electrode tab position. This reduces side reactions between the positive electrode active material and the electrolyte in the area corresponding to the negative electrode tab position, while also reducing the decomposition of the solid electrolyte membrane on the surface of the positive electrode sheet in the area corresponding to the negative electrode tab side. It can also reduce the impact of the products of side reactions between the negative electrode active material and the electrolyte on the structural stability of the positive electrode active material on the negative electrode tab side, suppressing gas and heat generation in the battery, and further improving the battery's thermal pack throughput and high-temperature cycle stability. On the other hand, the second surface coating can isolate the positive and negative electrodes, reducing the risk of short circuits caused by thermal shrinkage of the separator in this area at high temperatures, thus improving the battery's thermal pack throughput. In addition, by placing the second surface coating on the positive electrode side, combined with the solid electrolyte in the positive electrode active layer, the positive electrode dynamic performance is ensured while improving the thermal pack throughput and high-temperature cycling stability, thereby enhancing the battery's dynamic performance.
[0044] In this invention, the thickness of the second surface coating is h2, and h2 and R1 satisfy: 0.15≤h2 / R1≤60, for example, 0.15, 0.2, 0.3, 0.5, 1, 1.5, 2, 3, 4, 6, 8, 10, 15, 20, 25, 30, 35, 40, 45, 55 or 60.
[0045] In one embodiment, h2 and R1 satisfy: 1≤h2 / R1≤6.5.
[0046] In this invention, h2 is 0.5μm to 12μm, for example, 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 8μm, 10μm or 12μm. h2 can be determined by conventional testing methods in the art, such as SEM testing. The testing method can be the same as the test for h1, except that a fold of the positive electrode sheet opposite to the negative electrode tab groove is used to test the thickness h2 of the second surface coating.
[0047] In one embodiment, h2 is 1 μm to 8 μm.
[0048] In this invention, along the length direction of the positive electrode sheet, the ratio of the width of the negative electrode tab groove to the width of the third part is 0.05 to 0.5, for example, 0.05, 0.06, 0.08, 0.1, 0.15, 0.2, 0.25, 0.3, 0.4 or 0.5.
[0049] In this invention, along the length direction of the positive electrode sheet, the ratio of the width of the second groove to the width of the fourth portion is 0.05 to 0.5, for example, 0.05, 0.06, 0.08, 0.1, 0.15, 0.2, 0.25, 0.3, 0.4 or 0.5.
[0050] When h2 / R1 is too small (e.g., <0.15), h2 is too small compared to R1, causing solid electrolyte particles to protrude from the surface of the second surface coating. This reduces the surface smoothness and continuity of the second surface coating, increasing the interfacial resistance between the second surface coating and the positive electrode active layer. Simultaneously, it reduces the bonding tightness between the positive electrode active layer and the second surface coating, preventing the second surface coating from reducing side reactions between the positive electrode active layer and the electrolyte in areas of high localized temperature on the electrode. Consequently, it fails to improve the battery's thermal conductivity and high-temperature cycle stability. Furthermore, excessively large solid electrolyte particles have a small specific surface area and cannot effectively fill the gaps between the positive electrode active material particles, hindering their interaction with the positive electrode active material. With a small contact area, the efficiency of lithium-ion transport between particles is not significantly improved, which is not conducive to further improvement of cathode kinetics and thermal pack throughput. When h2 / R1 is too large (e.g., >60), h2 is too large compared to R1, the second surface coating is too thick, and the transport distance of lithium ions in the second surface coating is too large. Even if a solid electrolyte is introduced into the cathode active layer, it cannot take advantage of its high ionic conductivity, and the improvement of cathode kinetics is limited, which is not conducive to the improvement of battery rate performance. In addition, when R1 is small, although it can improve the lithium-ion transport rate, its large specific surface area will further reduce the structural stability of the cathode active material, thereby deteriorating the battery's thermal pack throughput and high-temperature cycling stability.
[0051] When h1 and / or h2 are too small (e.g., <0.5μm), it is difficult to form a continuous and dense surface coating in the positive electrode active layer area where the positive electrode tab groove is located and the corresponding positive electrode active layer surface where the negative electrode tab groove is located. Excessive exposure of the positive electrode active layer in areas with large heat accumulation on the positive electrode sheet to the electrolyte exacerbates the oxidative decomposition of the electrolyte and the impact of electrolyte by-reaction products on the structural stability of the positive electrode active material. It is impossible to reduce the structural damage of the positive electrode material by by-reaction products, which is not conducive to further improving the battery's thermal conductivity and high-temperature cycle stability. When h1 and / or h2 are too large (e.g., >12μm), the lithium ion transport path increases, leading to an increase in the internal resistance of the positive electrode sheet. At the same time, the excessively thick surface coating will increase the proportion of inactive materials, resulting in a loss of battery energy density. When h1 and / or h2 are too large, it also makes the local distance between the positive and negative electrode sheets of the battery large, increasing the lithium ion transport path or reducing the adhesion stability between the separator and the positive and negative electrode sheets, reducing the consistency of the internal electrochemical reaction of the battery, which is not conducive to further improving the battery's electrical performance.
[0052] In this invention, based on the total mass of the positive electrode active layer, the mass content of the solid electrolyte material is 0.1% to 2%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8% or 2%.
[0053] In one embodiment, the mass content of the solid electrolyte is 0.5% to 1.5% based on the total mass of the positive electrode active layer.
[0054] When the mass content of solid electrolyte in the positive electrode active layer is within the range of 0.5% to 2%, it ensures that there are enough solid electrolyte particles in the positive electrode active layer to form a preliminary ion conduction pathway and stabilize the interface, while also ensuring that the energy density of the battery is not affected. When the content of solid electrolyte in the positive electrode active layer is too low (e.g., <0.5%), insufficient solid electrolyte cannot build a sufficient ion pathway in the positive electrode active layer, which is not conducive to further improvement of the battery's rate performance. When the content of solid electrolyte in the positive electrode active layer is too high (e.g., >2%), excessive solid electrolyte will bring additional side reactions, which will increase electrolyte side reactions and be detrimental to further improvement of the battery's thermal safety performance.
[0055] In this invention, the positive electrode active layer includes at least one of the elements P, La, Ta and Ge; In this invention, based on the total mass of the positive electrode active layer, the mass content of the P element is 200ppm to 3000ppm, for example, 200ppm, 300ppm, 400ppm, 500ppm, 600ppm, 800ppm, 1000ppm, 1200ppm, 1400ppm, 1600ppm, 2000ppm, 2500ppm or 3000ppm.
[0056] In one embodiment, the mass content of P element is 300ppm to 2500ppm based on the total mass of the positive electrode active layer.
[0057] In this invention, based on the total mass of the positive electrode active layer, the mass content of La element is 200ppm to 4500ppm, for example, 200ppm, 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1200ppm, 1400ppm, 1600ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm or 4500ppm.
[0058] In one embodiment, the mass content of La element is 400ppm to 3000ppm based on the total mass of the positive electrode active layer.
[0059] In this invention, the solid electrolyte material includes an oxide-type solid electrolyte, which includes at least one of lithium aluminum titanium phosphate (LATP), lithium lanthanum zirconium oxide (LLZO), lithium lanthanum zirconium tantalum oxide (LLZTO), and lithium aluminum germanium phosphate (LAGP).
[0060] The content of characteristic elements in solid electrolytes directly determines the lattice parameters and the size of ion transport channels. For example, LATP or LAGP crystal structures are NASICON type, and lithium ions are transported through three-dimensional channels. If the phosphorus (P) content in the positive electrode active layer is too low (e.g., <200 ppm), the phosphate structure in the solid electrolyte lattice will be incomplete, leading to narrowing or blockage of lithium ion transport channels and a decrease in the ionic conductivity of the solid electrolyte. This is not conducive to effectively compensating for the increased ion transport resistance introduced by the surface coating. When the P content in the positive electrode active layer is too high (e.g., >3000 ppm), it may cause inactive substances to precipitate and block the ion transport channels. This leads to increased interfacial impedance, which is detrimental to improving the rate performance of the battery. LLZO and LLZTO have garnet-type crystal structures. When the La content in the positive electrode active layer is too low (e.g., <200ppm), the crystal structure is unstable and prone to collapse, resulting in decreased structural stability of the positive electrode sheet, which is detrimental to further improvement of the battery's thermal conductivity and high-temperature cycling stability. When the La content in the positive electrode active layer is too high (e.g., >4500ppm), it may cause lattice distortion, affecting lithium-ion transport. In addition, it may also form a high-resistivity phase at the grain boundaries, similarly increasing the resistance to charge transfer and hindering the improvement of the battery's rate performance.
[0061] In this invention, the mass content of P and La elements in the positive electrode active layer can be obtained by conventional testing methods in the art, for example, by the following method: after discharging the battery to 0% SOC, disassemble and remove the positive electrode sheet, soak it in DMC solvent for 12 hours, then rinse it with DMC to remove the lithium salt attached to the positive electrode sheet, then keep the positive electrode sheet at 450°C for 180 minutes, and brush off the positive electrode active layer from the cooled positive electrode sheet with a brush; take the collected positive electrode active layer powder as a sample, take about 0.1g of the sample and add 10mL of hydrochloric acid for digestion on a 350°C hot plate for 10 minutes, cool it and make up the volume to 100ml, then dilute it 10 times, and take a portion of the solution for analysis using an ICP spectrometer to obtain the mass content of P and La.
[0062] In this invention, the first and second surface coatings each independently comprise filler particles, which include at least one of aluminum hydroxide, magnesium hydroxide, boron nitride (BN), silicon dioxide, ammonium polyphosphate (APP), polytetrafluoroethylene (PTFE), and melamine cyanurate. The first and / or second surface coatings containing filler particles can prevent direct contact between the electrolyte and the positive electrode active material in areas with higher heat, reducing electrolyte side reactions.
[0063] In this invention, the first surface coating and the second surface coating each independently further include an adhesive, said adhesive comprising at least one of polyvinylidene fluoride (PVDF), polyimide (PI) precursor, polyamide-imide (PAI), styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber-sodium carboxymethyl cellulose composite system, polyacrylonitrile (PAN) based latex, polyacrylic acid (PAA), and polyacrylates.
[0064] In one embodiment, the polyacrylates include crosslinked modified acrylates, wherein the crosslinked modified acrylates include at least one of polyacrylic acid, lithium polyacrylate, sodium polyacrylate, polyacrylic acid-polyacrylonitrile copolymer polymethyl methacrylate.
[0065] In one embodiment, the polyvinylidene fluoride (PVDF) comprises homopolymer PVDF. Homopolymer PVDF has higher crystallinity and lower swelling degree than copolymer PVDF, and can maintain structural stability in the electrolyte.
[0066] PI precursors and PAI have higher heat resistance and mechanical strength. The styrene-butadiene rubber-sodium carboxymethyl cellulose composite system has good compatibility with the negative electrode active layer. PAN-based latex and polyacrylates can provide better flexibility and electrolyte resistance.
[0067] In this invention, the filler particles are at least partially embedded in the surface of the positive electrode active layer on the side away from the positive electrode current collector. The average embedding depth of the filler particles in the positive electrode active layer is d, which is 0.01 μm to 2 μm, for example, 0.01 μm, 0.05 μm, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.6 μm, 0.8 μm, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, or 2 μm. "At least partially" means that the proportion of the filler particles embedded in the positive electrode active layer to the total number of filler particles is greater than 0%, and can be less than 100% or equal to 100%. "Embedded" can be understood as the positive projected area of the filler particles overlapping with the positive electrode active layer along the thickness direction of the positive electrode sheet, and the overlap rate can be less than 100% or equal to 100%.
[0068] In this invention, the particle size Dv50 of the filler particles is R2, and R2 is 0.01μm~3μm, for example, 0.01μm, 0.02μm, 0.04μm, 0.06μm, 0.08μm, 0.1μm, 0.2μm, 0.4μm, 0.6μm, 1μm, 1.5μm, 2μm, 2.5μm or 3μm.
[0069] In this invention, d and R2 satisfy: 0.1≤d / R2≤0.6, for example, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55 or 0.6.
[0070] In one embodiment, d and R2 satisfy: 0.2≤d / R2≤0.4.
[0071] When R2 is too small (e.g., <0.01μm), the filler particles are prone to agglomeration, resulting in poor coating uniformity of the first and / or second surface coatings. This easily leads to localized stress concentration points. The extrusion of the positive electrode material after rolling also reduces the density of the first and / or second surface coatings, thus lowering the battery's thermal safety performance. When R2 is too large (e.g., >3μm), the large particle size of the filler particles makes it difficult to coat the first and / or second surface coatings thinly, reducing the lithium-ion transport performance in the battery and even affecting the battery's energy density. At the same time, the large particle size of the filler particles makes the interfacial contact between the first and / or second surface coatings and the positive electrode active layer unstable. During battery charging and discharging, they are prone to detachment under expansion stress, leading to the failure of the first and / or second surface coatings.
[0072] When filler particles are embedded in the positive electrode active layer, they can be effectively fixed in the active layer through cluster embedding or stacking anchoring, improving the bonding force between the first and / or second surface coatings and the positive electrode active layer. This ensures that they maintain stable interfacial contact with the positive electrode active layer even under the expansion stress of the silicon-carbon negative electrode, preventing local detachment or peeling that could lead to the failure of the first and / or second surface coatings. Adjusting d / R2 within a suitable range ensures that the filler particles form a strong mechanical interlocking structure after rolling, without losing the function of the first and / or second surface coatings in protecting the positive electrode, suppressing electrolyte side reactions, and preventing short circuits between the positive and negative electrodes. When d / R2 is too large (e.g., >0.6), d is too large relative to R2, resulting in excessive embedding depth of the filler particles in the positive electrode active layer. This may excessively compress the positive electrode active layer, damaging its internal conductive network and hindering the improvement of battery rate performance. When d / R2 is too small (e.g., <0.1), the mechanical interlocking effect between the filler particles and the positive electrode active layer is weak, resulting in insufficient mechanical stability under expansion stress and easy detachment and failure.
[0073] In this invention, d can be measured by conventional testing methods in the art, such as by SEM measurement, specifically as follows: Discharge to 0% SOC, disassemble and remove the positive electrode sheet, or directly remove the positive electrode sheet, soak and clean it with DMC and then dry it, select a fold of the positive electrode sheet where the positive electrode tab groove is located or a fold of the positive electrode sheet where the area opposite to the negative electrode tab groove is located, and after processing by argon ion polishing technology, a cross-sectional sample of the positive electrode sheet can be obtained. The obtained cross-section is imaged under SEM and the area containing both the first surface coating and the second surface coating is selected; in the selected area, the straight line (parallel to the positive electrode current collector) where the distance from the outline of the positive active material particle to the positive current collector is the largest is used as the baseline, and at least 5 different points are selected on the outline of the surface coating embedded in the positive active layer, the vertical distance from the points to the baseline is measured and the average value is taken as d.
[0074] In this invention, R2 can be measured by conventional testing methods in the art, for example, by referring to the test of R1.
[0075] In this invention, the electrode assembly includes an arcuate region and a flat region located between the arcuate regions, wherein the first surface coating and / or the second surface coating is located in the flat region.
[0076] In one embodiment, the electrode assembly includes an arcuate region and a flat region located between the arcuate region, with the first surface coating located in the flat region.
[0077] In one embodiment, the electrode assembly includes an arcuate region and a flat region located between the arcuate region, with the second surface coating located in the flat region.
[0078] In this invention, the first surface coating and / or the second surface coating extends from the flat area and at least partially covers at least one of the arcuate areas adjacent to the flat area. Here, "at least partially covers" can be understood as the percentage of the projected area of the first surface coating and / or the second surface coating on the arcuate area adjacent to the flat area being greater than 0%, and can be less than 100% or equal to 100%.
[0079] In one embodiment, the first surface coating extends from the flat area and at least partially covers at least one of the arcuate areas adjacent to the flat area.
[0080] In one embodiment, the second surface coating extends from the flat area and at least partially covers at least one of the arcuate areas adjacent to the flat area.
[0081] In some embodiments, the spacing between the first surface coating and the second surface coating is greater than 0 along the length direction of the positive electrode sheet, that is, the first surface coating and the second surface coating are non-continuous coatings.
[0082] In some embodiments, the first surface coating and the second surface coating are connected along the length direction of the positive electrode sheet.
[0083] In this invention, the negative electrode active layer includes a negative electrode active material, and the negative electrode active material further includes graphite.
[0084] In this invention, the average particle size of the silicon-carbon material is 3μm to 15μm, for example, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 10μm, 12μm, 14μm, or 15μm. The average particle size of the silicon-carbon material can be obtained by conventional testing methods in the art, for example, by discharging the battery to 0% SOC, disassembling and removing the negative electrode, or directly removing the negative electrode, polishing its cross-section with an argon ion mill, and then imaging the obtained cross-section using backscatter imaging mode in an SEM device; the silicon-carbon particles in the image appear grayish-white, and then the particle size is measured and the distribution is statistically analyzed using electron microscopy image analysis software such as ImageJ, measuring at least 50 different silicon-carbon particles to obtain the average particle size of the silicon-carbon material.
[0085] In one embodiment, the average particle size of the silicon-carbon material is 5 μm to 10 μm.
[0086] In this invention, the sphericity of the silicon-carbon material is greater than or equal to 0.8, for example, 0.8, 0.82, 0.84, 0.86, 0.9, 0.92, 0.94, 0.96, 0.98, or 1. The sphericity of the silicon-carbon material can be obtained by conventional testing methods in the art, for example, by discharging the battery to 0% SOC, disassembling and removing the negative electrode sheet, or directly removing the negative electrode sheet, polishing its cross-section with an argon ion mill, and then imaging the obtained cross-section using backscatter imaging mode in an SEM device; analyzing the image of each silicon-carbon particle in the SEM image of the negative electrode active layer at a certain magnification (e.g., 2500x) using image processing software such as Image Pro Plus, obtaining the perimeter and area of each particle, calculating the equivalent radius a1 and equivalent radius a2 of the perimeter of each silicon-carbon particle respectively, then the sphericity of each particle is a2 / a1, and then taking a weighted average of the sphericity of each particle to obtain the sphericity of the silicon-carbon material.
[0087] In this invention, the silicon-carbon material includes a carbon layer that covers at least a portion of the outer surface of the silicon-carbon material; wherein, "at least a portion" can be understood as the area of the carbon layer projected onto the surface of the silicon-carbon material being greater than 0%, and may be less than 100% or equal to 100%.
[0088] In this invention, the average thickness of the carbon layer is 2nm to 25nm, for example, 2nm, 4nm, 6nm, 8nm, 10nm, 12nm, 14nm, 16nm, 18nm, 20nm, or 25nm. The thickness of the carbon layer can be measured by conventional testing methods in the art, such as using a transmission electron microscope (TEM). After preparing the silicon-carbon material sample, it is imaged under the TEM. After magnification to a certain level, the carbon layer is determined based on the interface. Five different silicon-carbon material particles are randomly selected, and the thickness of the carbon layer is measured at five different locations, and the average value is taken.
[0089] In one embodiment, the average thickness of the carbon layer is 3 nm to 20 nm.
[0090] In one embodiment, the carbon layer comprises amorphous carbon.
[0091] In this invention, based on the total mass of the negative electrode active layer, the mass content of silicon element is 5% to 60%, for example, 5%, 6%, 8%, 10%, 12%, 14%, 16%, 20%, 25%, 30%, 40%, 50%, or 60%. The mass content of silicon element in the negative electrode active layer can be tested by conventional methods in the art. For example, after discharging the battery to 0% SOC, the negative electrode sheet is disassembled, soaked in DMC solvent for 12 hours, then rinsed with DMC solvent to remove the lithium salt attached to the negative electrode sheet, dried, and then subjected to high-temperature treatment at 400°C in an inert atmosphere for 2 hours (e.g., in a tube furnace under nitrogen or argon atmosphere). The negative electrode active layer can then be peeled off from the negative electrode current collector and collected as a test sample. Using a thermogravimetric analyzer (e.g., a TGA550 thermogravimetric analyzer), the sample size is 5-15 mg. Under an air or oxygen atmosphere, the temperature is increased from room temperature (25°C) to 900°C at a rate of 10°C / min, and held at 900°C for 40 min. This allows the non-silicon components in the negative electrode active layer to volatilize while the silicon is fully oxidized to silicon dioxide. The remaining substance is the ash content of the negative electrode active layer. The mass content of silicon in the negative electrode active layer can be calculated based on the mass of the ash, using the following formula: Mass content of silicon in the negative electrode active layer = 7 × mass of ash / (15 × mass of test sample).
[0092] Silicon-carbon materials with a sphericity greater than or equal to 0.8 are used. These materials are approximately spherical, and during battery charging and discharging, the expansion stress is uniformly distributed along the spherical surface of the silicon-carbon material, avoiding particle breakage and repeated SEI film regeneration caused by localized stress concentration. Silicon-carbon particles with a sphericity greater than or equal to 0.8 have good flowability and are uniformly dispersed in the slurry. The resulting negative electrode sheet has a high surface flatness and uniform silicon-carbon material distribution, reducing stress concentration points. Furthermore, the silicon-carbon material surface contains a carbon layer. This carbon layer reduces direct contact between the electrolyte and the silicon material, mitigating electrolyte side reactions and reducing the impact of side reaction products on the stability of the positive electrode structure. It also improves the conductivity of the negative electrode sheet, thereby enhancing its kinetics.
[0093] The positive electrode of the present invention has a surface coating at a specific location, which, when combined with the silicon-carbon negative electrode, can effectively address the high heat generation and low conductivity characteristics of the silicon-carbon negative electrode, thereby comprehensively improving the stability of the battery in hot box testing and long-term cycling.
[0094] In this invention, the positive electrode active layer comprises a positive electrode active material, which comprises lithium cobalt oxide. The average particle size of the lithium cobalt oxide is R3, which is 5μm to 25μm, for example, 5μm, 6μm, 7μm, 8μm, 10μm, 12μm, 14μm, 16μm, 20μm, 24μm, or 25μm. R3 can be obtained by conventional testing methods in the art, for example, by discharging the battery to 0% SOC, disassembling and removing the positive electrode sheet, polishing its cross-section with an argon ion milling machine, observing it under SEM at a certain magnification, and measuring the maximum diameter of at least 20 different lithium cobalt oxide particles using image analysis software (such as ImageJ) and taking the average value, which is R3.
[0095] In this invention, the positive electrode active layer includes a positive electrode active material, the positive electrode active material includes lithium cobalt oxide, the lithium cobalt oxide includes a first element, the first element includes at least one of the elements Al, Mg, Ti and Zr.
[0096] In one embodiment, the first element includes elements Al and Mg.
[0097] In yet another embodiment, the first element includes elements Al and Ti.
[0098] In yet another embodiment, the first element includes elements Mg and Ti.
[0099] In a further embodiment, the first element includes elements Al, Ti, and Mg.
[0100] In this invention, the mass ratio of elements Al, Mg and Ti is (0.2~2):(0.2~2):(0.2~2), for example, "0.5~2" can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.8, 1, 1.2, 1.4, 1.6, 1.8 or 2.
[0101] In this invention, based on the total mass of the lithium cobalt oxide, the total content of the first element is 5000ppm to 25000ppm, for example, 5000ppm, 5100ppm, 5200ppm, 5400ppm, 5600ppm, 6000ppm, 7000ppm, 8000ppm, 10000ppm, 15000ppm, 20000ppm, 22000ppm, 24000ppm, or 25000ppm. The total mass content of the first element in the lithium cobalt oxide can be determined by conventional testing methods in the art, such as by inductively coupled plasma spectrometry (ICP). Specifically, approximately 0.1g of lithium cobalt oxide is added to 10mL of hydrochloric acid and digested on a hot plate at 350℃ for 10min. After cooling, the volume is adjusted to 100mL, then diluted 10 times, and a portion of the solution is analyzed using an ICP spectrometer to obtain the content of the first element.
[0102] In one embodiment, the total content of the first element is 12,000 ppm to 18,000 ppm based on the total mass of the lithium cobalt oxide.
[0103] In this invention, R2 and R3 satisfy: R3 / R2≥5, for example, 5, 6, 8, 10, 15, 20, 25, 30, 40, 50, 100, 150, 200, 300, 400 or 500.
[0104] In one embodiment, R2 and R3 satisfy: 35 ≤ R3 / R2 ≤ 320.
[0105] Doping lithium cobalt oxide with a first element (e.g., Al, Mg, Ti, Zr) can stabilize the crystal structure, suppress phase transitions and oxygen evolution during high-temperature and high-pressure cycling, reduce side reactions between the positive electrode active material and the electrolyte, and allow the first and / or second surface coatings to adhere stably to the surface of the positive electrode active layer for protection. When the total content of the first element is too low (e.g., <5000ppm), it is difficult for the first element to stabilize the lithium cobalt oxide crystal structure and active oxygen, which is detrimental to improving the stability of the positive electrode structure. When the total content of the first element is too high (e.g., >25000ppm), excessive doping of the first element can cause lattice distortion or the formation of impurity phases in lithium cobalt oxide, increasing the positive electrode impedance. At the same time, excessive first element is also detrimental to the improvement of battery energy density and rate performance.
[0106] By adjusting R3 / R2≥5, it can be ensured that the filler particles can effectively fill the gaps between the lithium cobalt oxide particles and partially embed themselves on their surface. The resulting positive electrode has a dense structure, which improves the interfacial bonding strength, electrode flatness, and ion transport kinetics, thereby enhancing the battery's thermal performance and cycle stability.
[0107] In this invention, the term "0% SOC" refers to the battery being discharged at 0.1C to the lower limit voltage (e.g., 3.0V).
[0108] In this invention, the battery is a lithium-ion secondary battery.
[0109] It should be noted that the numerical designations such as "first" and "second" in this invention are only used to distinguish different substances or methods of use, and do not represent a difference in order.
[0110] The present invention will be described in detail below through embodiments. The embodiments described herein are only a part of the embodiments of the present invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0111] In the following examples, unless otherwise specified, all materials used are commercially available analytical grade.
[0112] The following examples illustrate the battery of the present invention.
[0113] Example 1: (1) Preparation of negative electrode: A negative electrode slurry was prepared by mixing the negative electrode active material (80% artificial graphite + 20% silicon carbide material), conductive carbon black, styrene-butadiene rubber, and sodium carboxymethyl cellulose in deionized water at a mass ratio of 96.1:0.5:2:1.4 and stirring until homogeneous. The negative electrode slurry was then uniformly coated onto both sides of a copper foil to obtain a negative electrode active layer. The negative electrode was then dried, rolled, and slit to obtain a negative electrode sheet. The negative electrode active layer was removed by laser at a specific position on the third surface of the negative electrode sheet to obtain a negative electrode tab groove. A copper-plated nickel tab was ultrasonically welded into this groove to obtain a negative electrode tab. The negative electrode active layer was removed from the fourth surface of the negative electrode sheet at a position opposite to the negative electrode tab groove to obtain a second groove.
[0114] The silicon-carbon material has an average particle size of 8.6 μm, a sphericity of 0.915, a carbon coating layer with a thickness of 8 nm, and a silicon content of 9.6% in the negative electrode active layer.
[0115] (2) Preparation of the positive electrode: SiO2 (R2 is 0.14 μm) and PVDF adhesive were stirred evenly to prepare a surface coating slurry. The mass content of SiO2 was 90% and the mass content of PVDF adhesive was 10% on a dry weight basis. Lithium cobalt oxide (R3 = 5.2 μm), solid electrolyte LATP (R1 = 3.2 μm), conductive agent (conductive carbon black and carbon nanotubes mixed at a mass ratio of 1:1), and PVDF at a mass ratio of 96.9:1.3:1:0.8 were placed in N-methylpyrrolidone (NMP) and stirred evenly to prepare a positive electrode slurry. The positive electrode slurry was uniformly coated on both sides of an aluminum foil to obtain a positive electrode active layer, leaving a single-sided area as the outermost layer of the core. A surface coating slurry was coated on specific positions on the first and second surfaces of the positive electrode sheet to obtain the first and second parts of the first surface coating, and the third and fourth parts of the second surface coating, respectively. The first surface coating and the positive electrode active layer located in the first and second parts were removed by laser to obtain the positive electrode tab groove and the first groove, respectively. After baking, rolling, and slitting, a positive electrode sheet was obtained. The orthogonal projection of the third part on the surface of the positive electrode sheet covered the orthogonal projection of the negative electrode tab groove, and the orthogonal projection of the fourth part on the surface of the positive electrode sheet covered the orthogonal projection of the second groove.
[0116] Wherein, h1 is 4.5 μm, h2 is 7.2 μm, h1 / R1 is 1.41, h2 / R1 is 2.25, the ratio of the width of the positive electrode tab groove to the width of the first part of the first surface coating is 0.1, the ratio of the width of the first groove to the width of the second part of the first surface coating is 0.1, the ratio of the width of the negative electrode tab groove to the width of the third part of the second surface coating is 0.1, the ratio of the width of the second groove to the width of the fourth part of the second surface coating is 0.1, the spacing between the first and second surface coatings is greater than 0; the mass content of P in the positive electrode active layer is 1821 ppm; the embedding depth d of SiO2 in the positive electrode active layer is 0.05 μm, d / R2 is 0.36; R3 / R2 is 37.1, the content of the first element in lithium cobalt oxide is 12150 ppm, and the mass content ratio of elements Al, Mg and Ti is 2:1:1.
[0117] (3) Preparation of electrolyte: Ethylene carbonate (EC), diethyl carbonate (DEC), and methyl ethyl carbonate (EMC) were mixed in a molar ratio of 1:1:1 to obtain a solvent. Based on the total mass of the electrolyte, 12% lithium hexafluorophosphate, 15% fluoroethylene carbonate (FEC), 1.5% 1,3,6-hexanetrionitrile (HTCN), and 2.5% 1,3-propanesulfonate lactone (PS) were added and stirred until homogeneous to obtain the electrolyte.
[0118] (4) Diaphragm: The diaphragm uses 5μm polyethylene (PE) as the base membrane. One side of the base membrane has a 1.5μm thick boehmite layer, and the surface of the boehmite layer is covered with a 1μm thick mixed adhesive layer of polymethyl methacrylate (PMMA) and PVDF. The other side of the base membrane has a 0.5μm thick PMMA adhesive layer.
[0119] (5) Battery fabrication: The battery is manufactured by rolling the above-mentioned slit and sheeted positive electrode, negative electrode and separator into a wound structure, and then performing hot pressing, encapsulation, liquid injection, formation and secondary sealing.
[0120] Example 2: Based on Example 1, the difference is: In the preparation of the negative electrode, the average particle size of the silicon-carbon material is 5.1 μm, the sphericity is 0.832, and the silicon-carbon material has a carbon coating layer with a thickness of 3 nm. In the preparation of the positive electrode sheet, the positive electrode slurry is obtained by mixing lithium cobalt oxide (R3 is 15.7 μm), LATP (R1 is 0.5 μm), conductive agent (conductive carbon black and carbon nanotubes mixed at a mass ratio of 1:1), and PVDF in NMP at a mass ratio of 96.9:1.3:1:0.8; R2 is 0.05 μm, h1 is 1.2 μm, h2 is 1.5 μm, h1 / R1 is 2.4, h2 / R1 is 3, the ratio of the width of the positive electrode tab groove to the width of the first part of the first surface coating is 0.4, and the ratio of the width of the first groove to the width of the second part of the first surface coating is... The ratio is 0.4; the ratio of the width of the negative electrode tab groove to the width of the third part of the second surface coating is 0.08; the ratio of the width of the second groove to the width of the fourth part of the second surface coating is 0.08; the spacing between the first and second surface coatings is greater than 0; the mass content of P in the positive electrode active layer is 2465 ppm; the embedding depth d of SiO2 in the positive electrode active layer is 0.02 μm; d / R2 is 0.4; R3 / R2 is 314; the content of the first element in lithium cobalt oxide is 14620 ppm; and the mass content ratio of elements Al, Mg and Ti is 1.5:0.5:0.5.
[0121] Example 3: Based on Example 1, the difference is: In the preparation of the negative electrode, the average particle size of the silicon-carbon material is 9.7 μm, the sphericity is 0.976, and the silicon-carbon material has a carbon coating layer with a thickness of 20 nm. In the preparation of the positive electrode sheet, the positive electrode slurry is obtained by mixing lithium cobalt oxide (R3 is 24.8 μm), solid electrolyte (a mixture of LATP and LLZO, R1 is 1.3 μm), conductive agent (a mixture of conductive carbon black and carbon nanotubes at a mass ratio of 1:1), and PVDF at a mass ratio of 97.4:0.8:1:0.8 in NMP; R2 is 0.2 μm, h1 is 8 μm, h2 is 6.5 μm, h1 / R1 is 6.15, h2 / R1 is 5, the ratio of the width of the positive electrode tab groove to the width of the first part of the first surface coating is 0.05, and the ratio of the width of the first groove to the width of the second part of the first surface coating is... The ratio is 0.05; the ratio of the width of the negative electrode tab groove to the width of the third part of the second surface coating is 0.5; the ratio of the width of the second groove to the width of the fourth part of the second surface coating is 0.5; the spacing between the first and second surface coatings is greater than 0; the mass content of P in the positive electrode active layer is 312 ppm; the mass content of La in the positive electrode active layer is 2978 ppm; the embedding depth d of SiO2 in the positive electrode active layer is 0.04 μm; d / R2 is 0.2; R3 / R2 is 124; the content of the first element in lithium cobalt oxide is 17680 ppm; and the mass content ratio of elements Al, Mg and Ti is 5:1:1.
[0122] Example 4: Based on Example 1, the difference is that R1 is 1.5 μm, h1 is 6 μm, h2 is 6 μm, h1 / R1 is 4, h2 / R1 is 4, d is 0.04 μm, and d / R2 is 0.29.
[0123] Example 5 group: This set of examples is used to verify the impact of changes in "R1", as follows: Example 5a is based on Example 1, except that R1 is 0.2 μm; Example 5b is based on Example 1, except that R1 is 4.9 μm.
[0124] Example 6 group: This set of examples is used to verify the impact of changes in "h1", as detailed below: Example 6a is based on Example 1, except that h1 is 0.6 μm; Example 6b is based on Example 1, except that h1 is 11.8 μm.
[0125] Example 7 group: This set of examples is used to verify the impact of changes in "h1 / R1", as detailed below: Example 7a is based on Example 1, except that R1 is 0.2 μm and h1 is 11.8 μm; Example 7b is based on Example 1, except that R1 is 4.9 μm and h1 is 0.8 μm; Example 7c is based on Example 2, except that h1 is 0.2 μm; Example 7d is based on Example 1, except that h1 is 13 μm.
[0126] Example 8 group: This set of examples is used to verify the impact of changes in "h2 / R1", as detailed below: Example 8a is based on Example 1, except that R1 is 0.2 μm and h2 is 11.8 μm; Example 8b is based on Example 1, except that R1 is 4.9 μm and h2 is 0.8 μm.
[0127] Example 9 group: This set of examples is used to verify the impact of changes in the "surface coating setting", as detailed below: Example 9a is based on Example 1, except that no second coating is provided on the positive electrode sheet; Example 9b is based on Example 1, except that the negative electrode does not have a second groove, and the positive electrode has a first part and a second part of the first surface coating and a third part of the second surface coating. Example 9c is based on Example 1, except that a first portion of the first surface coating is provided on the positive electrode sheet; Example 9d is based on Example 1, except that the first surface coating and the second surface coating are connected.
[0128] Example 10 group: This set of examples is used to verify the impact of changes in the "proportion of solid electrolyte in the positive electrode active layer", as detailed below: Example 10a, based on Example 3, except that the positive electrode slurry is prepared by mixing lithium cobalt oxide, solid electrolyte (LATP and LLZO), conductive agent (conductive carbon black and carbon nanotubes mixed in a mass ratio of 1:1) and PVDF in NMP in a mass ratio of 97.7:0.5:1:0.8. The mass content of P in the positive electrode active layer is 207 ppm and the mass content of La in the positive electrode active layer is 1463 ppm. Example 10b is based on Example 3, except that the positive electrode slurry is prepared by mixing lithium cobalt oxide, solid electrolyte (LATP and LLZO), conductive agent (conductive carbon black and carbon nanotubes mixed at a mass ratio of 1:1) and PVDF in NMP at a mass ratio of 96.3:1.9:1:0.8. The mass content of P in the positive electrode active layer is 2985 ppm, and the mass content of La in the positive electrode active layer is 4487 ppm.
[0129] Example 11 group: This set of examples is used to verify the impact of changes in the "selection of the first packing material", as detailed below: Example 11a is based on Example 1, except that the first filler is replaced with an equal mass of aluminum hydroxide, R2 is 2.7 μm, and d is 1.5 μm; Example 11b is based on Example 1, except that the first filler is replaced with an equal mass of melamine cyanurate, R2 is 1.5 μm and d is 0.2 μm.
[0130] Example 12 group: This set of examples is used to verify the impact of changes in "d / R2", as detailed below: Example 12a is based on Example 1, except that the first filler is replaced with an equal mass of melamine cyanurate, d is 0.15 μm, and R3 is 1.5 μm; Example 12b is based on Example 1, except that the first filler is replaced with an equal mass of melamine cyanurate, d is 0.12 μm, and R3 is 0.2 μm; Example 12c is based on Example 1, except that the first filler is replaced with an equal mass of melamine cyanurate, d is 0.1 μm, and R3 is 1.5 μm; Example 12d is based on Example 1, except that the first filler is replaced with an equal mass of melamine cyanurate, d is 0.16 μm and R3 is 0.2 μm.
[0131] Example 13 group: This set of examples is used to verify the impact of changes in "silicon-carbon materials", as detailed below: Example 13a is based on Example 1, except that the average particle size of the silicon-carbon material is 3.2 μm, the sphericity is 0.924, and the silicon-carbon material has a carbon coating layer with a thickness of 2 nm. Example 13b is based on Example 1, except that the silicon-carbon material has an average particle size of 14.9 μm, a sphericity of 0.906, and a carbon coating layer with a thickness of 25 nm.
[0132] Example 14 group: This set of examples is used to verify the impact of changes in the "mass content of silicon in the negative electrode active layer": Example 14a, based on Example 1, except that the negative electrode slurry is prepared by mixing negative electrode active material (82% artificial graphite + 18% silicon carbide material), conductive carbon black, styrene-butadiene rubber, and sodium carboxymethyl cellulose in deionized water at a mass ratio of 96.1:0.5:2:1.4 and stirring until homogeneous. The mass content of silicon in the negative electrode active layer is 5.2%. Example 14b is based on Example 1, except that the negative electrode slurry is prepared by mixing negative electrode active material (20% artificial graphite + 80% silicon carbide material), conductive carbon black, styrene-butadiene rubber, and sodium carboxymethyl cellulose in deionized water at a mass ratio of 96.1:0.5:2:1.4 and stirring until homogeneous. The mass content of silicon element in the negative electrode active layer is 53.8%.
[0133] Example 15 group: This set of examples is used to verify the impact of changes in the "mass content of the first element", as detailed below: Example 15a is based on Example 1, except that the content of the first element in lithium cobalt oxide is 5030 ppm; Example 15b is based on Example 1, except that the content of the first element in lithium cobalt oxide is 24,560 ppm.
[0134] Comparative Example 1: This set of proportions is used to verify the impact of changes in "h1 / R1", as detailed below: Comparative Example 1a is based on Example 1, except that R1 is 0.07 μm and h1 is 1 μm; Comparative Example 1b is based on Example 1, except that R1 is 6.3 μm and h1 is 1.2 μm; Comparative Example 1c is based on Example 1, except that R1 is 0.15 μm and h1 is 11.8 μm; Comparative Example 1d is based on Example 1, except that R1 is 4.9 μm and h1 is 0.6 μm.
[0135] Comparative Example 2: Based on Example 1, the difference is that the positive electrode active layer does not contain solid electrolyte, and the positive electrode slurry is prepared by mixing lithium cobalt oxide, conductive agent (conductive carbon black and carbon nanotubes in a mass ratio of 1:1) and PVDF in NMP in a mass ratio of 98.2:1:0.8 and stirring evenly.
[0136] Comparative Example 3: Based on Example 1, the difference is that the positive electrode does not have a first surface coating and a second surface coating.
[0137] Test example: 1. Hot box test: The batteries prepared in the embodiments and comparative examples of this invention were discharged at a constant current of 0.2C to the lower limit voltage at 25°C and allowed to stand for 5 minutes; then charged at a constant current of 0.5C to the upper limit voltage and kept at a constant voltage until the current dropped to 0.02C; the fully charged batteries were placed in a hot box and heated to 130°C at a heating rate of 5°C / min and held at that temperature for 60 minutes. Twenty batteries were tested, and the pass rate at 130°C and 132°C was recorded. A battery was considered pass if it did not ignite or explode, and fail if it ignited or exploded. The pass rate was recorded as n / 20, representing n out of 20 batteries passing. When testing at furnace temperatures of 130°C and 132°C, 20 batteries were tested at each temperature, and the results are recorded in Table 1.
[0138] 2. High-temperature cycling stability: At 45°C, the batteries prepared in the embodiments and comparative examples of this invention were discharged at 1C to 3.0V, then allowed to stand for 10 minutes, and then charged at 1C to 4.55V with a cutoff current of 0.025C, followed by a 10-minute stand. The thickness of the battery at this point was recorded as the initial thickness h1. The batteries were then discharged at a rate of 1.2C to the cutoff voltage of 3.0V, allowed to stand for 10 minutes, and the discharge capacity was recorded as the initial capacity. This charging and discharging process was repeated until the 600th cycle of constant voltage charging was completed, followed by a 10-minute stand. The batteries were then discharged at 1.2C to 3.0V, allowed to stand for 10 minutes, and the discharge capacity was recorded as the capacity after cycling. The cycle capacity retention rate is calculated as: Cycle Capacity × 100% / Initial Capacity. The results are recorded in Table 1.
[0139] 3. Ratio Performance Test: The batteries prepared in the embodiments and comparative examples of the present invention were tested at 25±5℃ for sample in-state voltage, internal resistance, and thickness; (1) rest for 5 min; (2) discharge at 0.2C to the lower limit voltage and record the discharge capacity Q1; (3) rest for 5 min; (4) charge at 0.7C to 4.55V in a constant temperature chamber, cut-off current 0.025C, constant voltage time 60 min; (5) rest for 5 min; (6) discharge at 3C to the lower limit voltage in a constant temperature chamber or constant temperature box environment; (7) rest for 5 min and record the discharge capacity Q2; the capacity retention rate at the 3C discharge rate is Q2 / Q1×100%. The results are recorded in Table 1.
[0140] Table 1: As can be seen from Table 1, the lithium-ion battery prepared by this invention balances rate performance and thermal safety performance compared to the comparative example.
[0141] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A battery, characterized in that, The electrode assembly includes a positive electrode sheet, a separator, and a negative electrode sheet wound together. The positive electrode sheet includes a positive current collector and a positive active layer located on both sides of the positive current collector. The negative electrode sheet includes a negative current collector and a negative active layer located on both sides of the negative current collector. The positive electrode active layer includes a solid electrolyte material, wherein the median particle size Dv50 of the solid electrolyte material is R1, and R1 is 0.1 μm to 5 μm; The negative electrode active layer includes a negative electrode active material, which includes silicon-carbon material. The positive electrode sheet includes a first surface and a second surface disposed opposite to each other along the thickness direction, and the first surface is provided with a positive electrode tab groove that exposes the positive electrode current collector; The positive electrode sheet further includes a first surface coating. Along the thickness direction of the positive electrode sheet, the first surface coating is located on the surface of the positive electrode active layer away from the positive electrode current collector. The first surface coating includes a first portion disposed around the positive electrode tab groove. The thickness of the first coating layer is h1, and h1 and R1 satisfy: 0.15≤h1 / R1≤60.
2. The battery according to claim 1, wherein, The second surface of the positive electrode sheet is provided with a first groove, and the first groove and the positive electrode tab groove are disposed opposite to each other along the thickness direction of the positive electrode sheet; the first surface coating also includes a second part disposed around the first groove; And / or, h1 is 0.5μm~12μm; preferably 1μm~8μm; And / or, R1 is 0.5μm~3μm; And / or, h1 and R1 satisfy: 1 ≤ h1 / R1 ≤ 6.5; And / or, along the length direction of the positive electrode sheet, the ratio of the width of the positive electrode tab groove to the width of the first portion is 0.05 to 0.
5.
3. The battery according to claim 1 or 2, wherein, The negative electrode sheet includes a third surface and a fourth surface disposed opposite to each other along the thickness direction, wherein the third surface is provided with a negative electrode tab groove that exposes the negative electrode current collector, and the negative electrode sheet also includes a negative electrode tab located in the negative electrode tab groove; The positive electrode sheet further includes a second surface coating layer located on the side of the positive electrode active layer away from the positive electrode current collector. The second surface coating layer includes a third portion. Along the thickness direction of the battery, the third portion is disposed opposite to the negative electrode tab groove. Along the thickness direction of the negative electrode sheet, the third portion and the negative electrode tab groove at least partially overlap the orthogonal projection of the negative electrode tab groove on the surface of the positive electrode sheet. Preferably, the fourth surface of the negative electrode sheet is further provided with a second groove, and the second groove and the negative electrode tab groove are disposed opposite to each other along the thickness direction of the negative electrode sheet. The second surface coating also includes a fourth part, and the fourth part and the second groove are disposed opposite to each other along the thickness direction of the battery. The orthographic projections of the fourth part and the second groove on the surface of the positive electrode sheet at least partially overlap.
4. The battery according to claim 3, wherein, The thickness of the second coating layer is h2, and h2 and R1 satisfy: 0.15≤h2 / R1≤60; preferably, 1≤h2 / R1≤6.5; And / or, h2 is 0.5μm~12μm; preferably, h2 is 1μm~8μm; And / or, along the length direction of the positive electrode sheet, the ratio of the width of the negative electrode tab groove to the width of the third portion is 0.05 to 0.
5.
5. The battery according to claim 1 or 2, wherein, Based on the total mass of the positive electrode active layer, the mass content of the solid electrolyte material is 0.1% to 2%; preferably 0.5% to 1.5%. And / or, the positive electrode active layer includes at least one of the elements P, La, Ta and Ge; Preferably, based on the total mass of the positive electrode active layer, the mass content of P element is 200ppm to 3000ppm; Preferably, based on the total mass of the positive electrode active layer, the mass content of La element is 200ppm~4500ppm; Preferably, the solid electrolyte material includes an oxide-type solid electrolyte, which includes at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, and lithium aluminum germanium phosphate.
6. The battery according to claim 3, wherein, The first and second surface coatings each independently comprise filler particles, the filler particles comprising at least one of aluminum hydroxide, magnesium hydroxide, boron nitride, silicon dioxide, ammonium polyphosphate, polytetrafluoroethylene, and melamine cyanurate; And / or, the first surface coating and the second surface coating each independently further include an adhesive, said adhesive comprising at least one of polyvinylidene fluoride, polyimide precursor, polyamide-imide, styrene-butadiene rubber, sodium carboxymethyl cellulose, styrene-butadiene rubber-sodium carboxymethyl cellulose composite system, polyacrylonitrile-based latex, polyacrylic acid, and polyacrylates.
7. The battery according to claim 6, wherein, The filler particles are at least partially embedded in the surface of the positive electrode active layer on the side away from the positive electrode current collector, and the average embedding depth of the filler particles in the positive electrode active layer is d, where d is 0.01 μm to 2 μm. And / or, the particle size Dv50 of the filler particles is R2, where R2 is 0.01μm~3μm; Preferably, d and R2 satisfy: 0.1 ≤ d / R2 ≤ 0.6; More preferably, d and R2 satisfy: 0.2≤d / R2≤0.
4.
8. The battery according to claim 3, wherein, The electrode assembly includes an arc-shaped region and a flat region located between the arc-shaped regions, with the first surface coating and / or the second surface coating located in the flat region; Preferably, the first surface coating and / or the second surface coating extend from the flat area and at least partially cover at least one of the arcuate areas adjacent to the flat area; More preferably, the spacing between the first surface coating and the second surface coating is greater than 0 along the length direction of the positive electrode sheet; More preferably, the first surface coating and the second surface coating are connected along the length direction of the positive electrode sheet.
9. The battery according to claim 1 or 2, wherein, The negative electrode active material also includes graphite; And / or, the average particle size of the silicon-carbon material is 3μm~15μm; preferably 5μm~10μm; And / or, the sphericity of the silicon-carbon material is greater than or equal to 0.8; And / or, the silicon-carbon material includes a carbon layer that covers at least a portion of the outer surface of the silicon-carbon material; Preferably, the average thickness of the carbon layer is 2nm~25nm; more preferably, it is 3nm~20nm. Preferably, based on the total mass of the negative electrode active layer, the mass content of silicon element is 5% to 60%.
10. The battery according to claim 7, wherein, The positive electrode active layer includes a positive electrode active material, which includes lithium cobalt oxide, and the average particle size of the lithium cobalt oxide is R3, where R3 is 5μm~25μm. And / or, the positive electrode active layer includes a positive electrode active material, the positive electrode active material includes lithium cobalt oxide, the lithium cobalt oxide includes a first element, the first element includes at least one of the elements Al, Mg, Ti and Zr; Preferably, based on the total mass of the lithium cobalt oxide, the total content of the first element is 5000ppm to 25000ppm; more preferably, it is 12000ppm to 18000ppm. Preferably, R2 and R3 satisfy: R3 / R2≥5; More preferably, R2 and R3 satisfy: 35≤R3 / R2≤320.